Integrasi lateral thinking dalam kurikulum sains: a systematic literature review - Cahyandaru, Pramudya; Nizhomi, Bestiana; Ame, Ibrahim Pandu; Nofrida, Eka Ridha (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
This research conducts a systematic literature review on the integration of lateral thinking into the science curriculum under the Merdeka Belajar Curriculum. The study evaluates the quality of existing science textbooks, highlights the need for effective teacher training, and explores the integration of lateral thinking with other learning approaches such as STEM and computational thinking. The findings from this review indicate that, despite an acknowledgement of the importance of lateral thinking in science education, there remains a shortcoming in textbooks and teaching methods that effectively support the development of these skills. Furthermore, the study also found that existing teacher training is inadequate to meet the needs of teaching that integrates lateral thinking. This study recommends the development of more supportive educational resources and training modules, as well as further research to optimize the integration of lateral thinking within the science curriculum.